REPRESENTATION OF THE MEANING OF TIME AND WOMEN IN THE FILM POSTER SORE: IITRI DARI MASA DEPAN: A STUDY OF VISUAL SEMIOTICS AS A DEVELOPMENT OF VISUAL LITERACY TEACHING MATERIALS - Muthia Azizah; Shafa Aida Zafira; Zahara Dafina Nurul 'Aisyah; Aliyah (Journal Informatic, Education and Management (JIEM), 2026)
The film poster for SORE: Istri dari Masa Depan by Yandy Laurens serves as a starting point for research to understand how time and women are represented in contemporary Indonesian visual culture, while also exploring its potential as a visual literacy teaching material. This study uses an interpretive qualitative semiotic approach with Roland Barthes' three-level framework of meaning—denotation, connotation, and myth—and is strengthened by in-depth interviews with five informants to obtain audience perceptions. The analysis focuses on five visual elements: color grading, lighting, layering, bird's-eye view framing, and typography. The research findings indicate that the composition of the spiral staircase depicts time as a non-linear cycle, while the doubling of female figures forms a fragmented and dreamy feminine identity. Furthermore, this study finds that the semiotic analysis of the film poster has real benefits as an authentic teaching material in the Visual Communication Design Study Program. Thus, this research confirms that film poster design is not just a visual communication medium, but also a critical learning resource worthy of being integrated into the visual communication education curriculum to develop students' visual literacy competencies.